ANALISIS INPUT-OUTPUT DAMPAK SEKTOR PARIWISATA TERHADAP PEREKONOMIAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Buana, Arya Galih; Ghefira Nurhaliza, Celine; Fauzan, Achmad; Sutisna, Irwan (LPPM Universitas Bina Bangsa, 2025)
The tourism sector plays an important role in increasing employment absorption, promoting equitable business opportunities, and contributing to foreign exchange earings. In 2023, optimism in Indonesia's tourism sector grew, with the number of domestic tourist trips reaching 825.80 million, an increase of 12.37 percent compared to 2022. The Special Region of Yogyakarta (DIY) is one of the most popular tourist destinations in Indonesia, known for its cultural, historical, and natural richness. The growth of tourist visits in DIY not only increases direct income from tourism activities but also positively impacts other economic sectors such as culinary, handicrafts, transportation, and services. This study aims to analyze the role of the tourism sector in DIY in driving and contributing to the regional economy using the Input-Output table. Backward and forward linkage analysis is used to identify key sectors in the economy. The results show that the air transportation sector has the highest spread value among other tourism sectors, while the food and beverage provision sub-sector contributes the most to the total Gross Regional Domestic Product (GRDP) at Current Market Prices in DIY. Simulations of a 1000 billion rupiah investment in each tourism sub-sector show that the air transportation sub-sector provides the largest total impact, while the food and beverage provision sub-sector makes a significant contribution to economic output. Employment projections indicate that the transportation and warehousing sector can create approximately 37,183 new jobs, while the accommodation and food and beverage sector can generate around 3,523 new jobs. Equal investment in each sub-sector is estimated to increase economic growth by 4.25% and reduce the number of unemployment people by 1.832%.